10.HODGKIN DISEASE IN CHILDREN (Iraqi Journal of Medical Sciences, 2019)
Background: Hodgkin lymphoma (HL) is a malignant process involving the lympho-reticular system that accounts for 6% of childhood cancers. Infectious agents may be involved, such as human herpes virus 6, cytomegalovirus, and Epstein-Barr virus (EBV). Infection with EBV confers a 4-fold higher risk of developing HL.Objective: To have an idea about the mode of presentation, pathological subtypes, treatment applied and outcome in one center in our country.Methods: A retrospective study was done whereby twenty cases were collected from the Pediatric Oncology Clinic in Al-Imamein AL-Kadhimein Medical City over a period of ten years from the first of January 2007 – end of December 2016. Information was taken from the patient’s records in the Pediatric Oncology Clinic including age at presentation, sex, physical finding, histopathological subtypes, staging , treatment applied and outcome.Results: Among the studied group, 14 cases (70%) were males and 6 cases (30%) were females, male: female ratio equal to 2.3:1, rang of age was between 5-12 years with a peak age at presentation was between 5-7 years, 12 cases (60%). The initial presentation was an enlarged cervical lymph node in 19 of them (95%), histopathologically, most of the patients had mixed cellularity subtype, 9 cases (45%), stage II and stage III comprise the majority of cases 9 cases (45%), 6 cases (30%) respectively, B symptoms were reported in 7 cases (35%). Chemotherapy was the mainstay of treatment with good response and remission, 17 cases (85%). Three cases refractory to treatment (15%) with no response, no death was reported.Conclusion: Male predominance was noticed with younger age group at presentation. The majority presented with enlarged cervical lymph node. Although mixed cellularity was encountered in most of the patients, the response to chemotherapy was good. Rituximab can be used along with chemotherapy for refractory cases and for lymphocyte predominant Hodgkin lymphoma.Keywords: Hodgkin Disease , ChildrenCitation: Abbas SA, Ali RH. Hodgkin disease in Children. Iraqi JMS. 2018; 16(4): 424-429. doi: 10.22578/IJMS.16.4.10
Keywords: Hodgkin Disease; Children